IMPACT OF AN EDUCATIONAL PROGRAM USING AUDITORY AND VISUAL FEEDBACK TO LEARN PRACTICAL PERFORMANCE ACCORDING TO PHYSICAL EDUCATION LESSON PLAN - Rafid Waleed Da'is (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. The background of this study is based on the importance of improving the quality of practical learning in physical education, particularly through the use of sensory-based feedback such as auditory and visual cues. Objectives. The purpose of this research was to investigate the impact of an educational program using auditory and visual feedback on enhancing students’ practical performance in accordance with the physical education lesson plan. Method. This study employed an experimental method suitable for the research objectives. The research population consisted of 58 third-stage female students from the Department of Theoretical Sciences, College of Physical Education and Sports Sciences, University of Basra, during the academic year 2023–2024. The sample was selected randomly by a lottery method based on class divisions. Class 1 consisted of 30 students, from which 8 students (26.66%) were selected for the experimental group that received auditory and visual feedback. Class 2 consisted of 28 students, from which 8 were randomly selected for the control group using traditional methods. Results. The results showed that the use of auditory and visual feedback led to a significant improvement in students' practical performance compared to the conventional teaching method. The data indicated a marked difference in skill enhancement between the experimental and control groups. Conclusion. The study concluded that the educational program based on auditory and visual feedback was effective in improving students' practical performance. Therefore, it is recommended that this approach be integrated into physical education learning programs, especially in preparation phases leading to practical application. The contribution of this study lies in providing empirical evidence on the effectiveness of sensory-based methods in practical learning processes and offering insights for pedagogical innovation in modern physical education curricula.